Answer:
Correct option: A. P=0.057
Step-by-step explanation:
<u>Binomial Distribution</u>
The binomial distribution fits the case of n independent events each one with a probability of success equal to p where k successes have been achieved.
The PMF (Probability Mass Function) of the binomial distribution is
![\displaystyle P(k,n,p)=\binom{n}{k}p^kq^{n-k}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%28k%2Cn%2Cp%29%3D%5Cbinom%7Bn%7D%7Bk%7Dp%5Ekq%5E%7Bn-k%7D)
Where ![q = 1-p](https://tex.z-dn.net/?f=q%20%3D%201-p)
The individual probability that an electronic device does not function properly is p=0.1. We know n=10 devices have been bought and we want to compute the probability that 7 devices function properly. Please notice that this is not the value of k since p is the probability of failure. The correct value of k=10-7=3. The required probability is
![\displaystyle P(3,10,0.1)=\binom{10}{3}0.1^30.9^{10-3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%283%2C10%2C0.1%29%3D%5Cbinom%7B10%7D%7B3%7D0.1%5E30.9%5E%7B10-3%7D)
![\boxed{P=0.057}](https://tex.z-dn.net/?f=%5Cboxed%7BP%3D0.057%7D)
Answer:
152°
Step-by-step explanation:
Let P be any point on tangent
and WY is secant or chord of the
.
NOW, by tangent secant theorem:
![m\angle WYP =\frac{1}{2}\times m(\widehat{WXY}) \\\\76°=\frac{1}{2}\times m( \widehat{WXY}) \\\\76°\times 2 =m( \widehat{WXY}) \\\huge \purple {\boxed {\therefore m(\widehat{WXY}) = 152°}}](https://tex.z-dn.net/?f=%20m%5Cangle%20WYP%20%3D%5Cfrac%7B1%7D%7B2%7D%5Ctimes%20m%28%5Cwidehat%7BWXY%7D%29%20%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E76%C2%B0%3D%5Cfrac%7B1%7D%7B2%7D%5Ctimes%20m%28%20%5Cwidehat%7BWXY%7D%29%20%5C%5C%5C%5C%3C%2Fp%3E%3Cp%3E76%C2%B0%5Ctimes%202%20%3Dm%28%20%5Cwidehat%7BWXY%7D%29%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Chuge%20%5Cpurple%20%7B%5Cboxed%20%7B%5Ctherefore%20m%28%5Cwidehat%7BWXY%7D%29%20%3D%20152%C2%B0%7D%7D%20)
Answer:
do distributive property on both, so multiply 6•x and 6•-4. then multiply 7•x and 7•3.
so it'll basically be 6x - 24 = 7x + 21.
then add 24 to both sides so: 6x - 24 + 24 = 7x + 21 + 24. since -24+24=0 it'll be 6x = 7x + 21 + 24.
then add 21 + 24 and that will be 45.
so 6x = 7x + 45
then subtract 7x from both sides 6x - 7x = 7x + 45 - 7x
that'll be -x = 7x + 45 - 7x
combine like terms (7x - 7x) = 0
so -x = 45
and since x can't be negative, do the opposite signs
so instead of -x = 45, make it x = -45
Hope it helped! (sorry that's its very long just wanted to show u the steps just in case)
Answer:
can i please have somepoints
Step-by-step explanation:
i need to get an answer to a question and if i don't i might fail a really hard test